2017
DOI: 10.1108/qmr-04-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Visual cues and innovation adoption among bottom of the pyramid consumers

Abstract: Purpose -To explore how visual comprehensibility of a product can affect innovation adoption among bottom of the pyramid consumers (BOP) in Bangladesh.Design/methodology/approach -This is an exploratory qualitative study based on interviews with 8 managerial respondents involved in the design and marketing of innovative products targeted at BOP consumers in Bangladesh, and 3 respondents who are consumers of these products. Originality/value -This is one of the first studies to consider innovation adoption of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Low consumer literacy adds emphasis to visual comprehension due to consumers' concrete rather than abstract thinking styles (Viswanathan & Gau, 2005). This suggests the need to use pictorial images, for example, to enhance comprehension (Hasan, Lowe & Rahman, 2017). Design should also ensure functionality compatible with cultural norms and constraints (Donaldson, 2006).…”
Section: Characteristics Of Subsistence Marketplacesmentioning
confidence: 99%
“…Low consumer literacy adds emphasis to visual comprehension due to consumers' concrete rather than abstract thinking styles (Viswanathan & Gau, 2005). This suggests the need to use pictorial images, for example, to enhance comprehension (Hasan, Lowe & Rahman, 2017). Design should also ensure functionality compatible with cultural norms and constraints (Donaldson, 2006).…”
Section: Characteristics Of Subsistence Marketplacesmentioning
confidence: 99%
“…Consumer preferences mainly include network, price, brand image, promotional offer, or internet speed. Herzog () found that brand image significantly influences technological innovation adoption, and Hasan et al () insisted that visual cues are a very important factor for BOP consumers' innovation adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All research of innovation adoption in the context of developed countries finds either well‐educated or non‐poor consumers to be considered as target markets. Few studies are evidenced concerning mobile payment adoption among BOP consumers, often characterized as having low literacy rates and limited numeracy skills (Hasan et al, ; Nakata & Weidner, ; Prahalad, ). Therefore, this article aims to explore further factors influencing mobile payment adoption among BOP consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The third theme is related to better understanding loyalty and satisfaction, how these are affected by resource availability and how consumers' loyalty to a supplier can be due simply to a lack of alternatives (Leonhardt and Chu, 2017;Sinha et al, 2017). The fourth theme addresses brand, product and retail, discussing how products or services affect both personal and financial well-being at the bottom of the pyramid, such as the use of online banking, the understanding and complexity of the product, purchasing structure, market pressures and retailers' decisions about adopting brands and retail (Leonhardt and Chu, 2017;Sinha et al, 2017;Hasan et al, 2017;Farooq, 2017). Suggestions are also made for long-term studies to assess consumer behavior over time and qualitative research such as ethnographies.…”
Section: Consumption At the Bottom Of The Pyramid: Current State Of Rmentioning
confidence: 99%